Corporate Governance, Political Connections, and Earnings Management - Ni Nyoman Iin Purnama Sari; Ni Wayan Rustiarini; Ni Putu Shinta Dewi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
This study aims to examine the effect of corporate governance and political connection on earnings management. The corporate governance variable was reviewed using four proxies: bonus compensation, institutional ownership, independent commissioners, and financial expertise of audit committees. The study was conducted on 183 manufacturing companies on the Indonesian Stock Exchange for three research periods, namely 2017-2019. This study uses multiple linear regression to test the research hypotheses. The results prove that bonus compensation improves earnings management, while institutional ownership is proven to reduce earnings management. However, the other three variables, namely independent board of commissioners, financial expertise of audit committee, and political connections, do not affect earnings management practices.